MORPHOLOGICAL FEATURES OF MIDDLE NECK CYSTS - Tursunov, Kh.Z.; Choriyev, B.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. According to scientific literature sources, neck cysts are a pressing problem in the field of maxillofacial surgery, with special attention paid to the sources of their development and morphological features. At the same time, the opinions of specialists about the mechanism of occurrence and the place of occurrence of this pathology in patients of different ages differ. The article analyzes preparations made from postoperative biopsy materials to study the cyst wall structure. The results obtained were compared with scientific literature sources. Methods. Nine patients with branchiogenic cysts were evaluated. Preparations stained with hemotoxicity and eosin were prepared from these tissues. Preparations were examined microscopically. Results. According to the results of our research, branchiogenic cysts make up 13.6% of neck and jaw tumours. Dystrophic changes of single-row flattened epithelial cells can be seen in purulent cysts, and areas of their desquamation were identified in the epithelial layer itself. Conclusions. In morphological studies, the histological structure of neck-side cysts generally corresponds to the information presented in scientific literature sources. Still, in some cases, it can be seen that its inner surface consists of multi-layered flat epithelium. To prevent the development of the disease, it is necessary to make an early diagnosis. BC is characterized as a tumor transformation of the normal epithelial lining of the cyst.